GPR15 in colon cancer development and anti-tumor immune responses - Namkoong, Hong; Lee, Bomi; Swaminathan, Gayathri; Koh, Seong-Joon; Rogalla, Stephan; Paraskevopoulou, Maria D.; Tang, Jay; Mikhail, David; Becker, Laren S.; Habtezion, Aida (Frontiers in Oncology, 2023)
Introduction The chemoattractant receptor, G protein-coupled receptor 15 (GPR15), promotes colon homing of T cells in health and colitis. GPR15 function in colon cancer is largely unexplored, motivating our current studies. Methods In human study, immune cells were isolated from tumor tissues and healthy surgical tumor margins (STM), and their proportions as well as expression of GPR15 was analyzed by flow cytometry. In mouse studies, colon cancer was induced in GPR15-deficient (KO) and GPR15-suficient (Het) mice using azoxymethane (AOM) and dextran sulfate sodium (DSS) solution in drinking water. Serial endoscopy was performed in mice to monitor and visualize the distal region of colon. Mice were euthanized 10 weeks after the initial DSS administration, and the colon length and the number of polyps were recorded. Next, we identified the effects of GPR15L on established tumors in the MC38-colorectal cancer (CRC) mouse model. Immune cells were isolated from the mice colons or tumors and assessed by flow cytometry. Results Our analysis of human CRC tissue revealed a significant reduction in GPR15+ immune cell frequencies in tumors compared to ‘tumor-free’ surgical margins. Similarly, our data analysis using The Cancer Genome Atlas (TCGA) indicated that lower GPR15 expression is associated with poor survival in human colon cancer. In the AOM/DSS colitis-associated colon cancer model, we observed increased colonic polyps and lower survival in Gpr15+-KO compared to Gpr15-Het mice. Analysis of immune cell infiltrates in the colonic polyps showed significantly decreased CD8+ T cells and increased IL-17+ CD4+ and IL-17+ CD8+ T cells in Gpr15-KO than in Het mice. Consistent with a protective role of GPR15, administration of GPR15L to established tumors in the MC38-CRC model increased CD45+ cell infiltration, enhanced TNFa expression on CD4+ and CD8+ T cells at the tumor site and dramatically reduced tumor burden. Discussion Our findings highlight an important, unidentified role of the GPR15-GPR15L axis in promoting a tumor-suppressive immune microenvironment and unveils a novel, colon-specific therapeutic target for CRC.